The London discount market - Scammell, W. M. (London Elek Books, 1968)
This book is concerned with the evolution and activities of the London discount market and with certain other branches of the money market which are closely connected with it. It explains the distinction between the discount houses and the money markets.
Includes index
Bibliography: p. 259-260.
occ 17/01/2019
Loans
Keywords: Discount; England - London